2015
DOI: 10.5056/jnm15027
|View full text |Cite
|
Sign up to set email alerts
|

Role of MicroRNA in Visceral Pain

Abstract: The long-lasting nociceptive transmission under various visceral pain conditions involves transcriptional and/or translational alteration in neurotransmitter and receptor expression as well as modification of neuronal function, morphology and synaptic connections. Although it is largely unknown how such changes in posttranscriptional expression induce visceral pain, recent evidence strongly suggests an important role for microRNAs (miRNAs, small non-coding RNAs) in the cellular plasticity underlying chronic vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 137 publications
(134 reference statements)
0
5
0
Order By: Relevance
“…While modifications to chromatin, such as acetylation or methylation of histones, are the most studied epigenetic mechanisms, modification of the DNA bases leading to enhanced or repressed transcription also influence overall gene expression (Bernstein et al, 2007 ). The definition of epigenetics has been expanded to include regulatory RNA sequences (microRNA [miRNA] or small non-coding RNA) due to their ability to affect mRNA translation (Farh et al, 2005 ; Zhang and Banerjee, 2015 ). While epigenetic mechanisms have been identified in some chronic neuropathic or inflammatory pain disorders, epigenetic regulation of chronic visceral pain is still an emerging field of research interest (Greenwood-Van Meerveld et al, 2016 ; Ligon et al, 2016 ).…”
Section: Epigenetic Mechanisms Mediating Stress-induced Chronic Viscementioning
confidence: 99%
“…While modifications to chromatin, such as acetylation or methylation of histones, are the most studied epigenetic mechanisms, modification of the DNA bases leading to enhanced or repressed transcription also influence overall gene expression (Bernstein et al, 2007 ). The definition of epigenetics has been expanded to include regulatory RNA sequences (microRNA [miRNA] or small non-coding RNA) due to their ability to affect mRNA translation (Farh et al, 2005 ; Zhang and Banerjee, 2015 ). While epigenetic mechanisms have been identified in some chronic neuropathic or inflammatory pain disorders, epigenetic regulation of chronic visceral pain is still an emerging field of research interest (Greenwood-Van Meerveld et al, 2016 ; Ligon et al, 2016 ).…”
Section: Epigenetic Mechanisms Mediating Stress-induced Chronic Viscementioning
confidence: 99%
“…There have also been some recent insights into the role that miRNAs play in experimental visceral pain models of chronic cystitis and esophageal reflux disease, with several miRNAs identified in the development of chronic visceral pain (Sengupta et al, 2013;Zhang and Banerjee, 2015). However, evidence directly linking these miRNAs to visceral pain behaviors is currently lacking.…”
Section: Evidence For Epigenetic Changes In Preclinical Studies Of Painmentioning
confidence: 99%
“…It has been speculated that these ncRNAs are emerging key regulators of gene expression under physiological and pathological conditions (Wang and Chang, 2011; Yang et al, 2014; Li et al, 2016). Moreover, emerging data have shown that ncRNAs are of crucial importance in various types of pain, particularly NP (Chen et al, 2014; Shao et al, 2015; Zhang and Banerjee, 2015; Wang et al, 2016). However, the regulatory functions of ncRNAs in NP and their underlying functional mechanisms have not been systematically described.…”
Section: Introductionmentioning
confidence: 99%